Platelet-rich plasma ameliorates senescence-like phenotypes in a cellular photoaging model. Issue 6 (13th January 2017) - Jia, Chuanlong; Lu, Yongzhou; Bi, Bo; Chen, Liang; Yang, Qingjian; Yang, Ping; Guo, Yu; Zhu, Jingjing; Zhu, Ningwen; Liu, Tianyi
Abstract : Platelet-rich plasma (PRP) is a portion of blood plasma enriched with platelets widely investigated for accelerating bone and soft tissue healing. Abstract : Background : Platelet-rich plasma (PRP) is a portion of blood plasma enriched with platelets widely investigated for accelerating bone and soft tissue healing. The purpose of this study is to evaluate the effects of PRP on the previous established photoaging model in vitro and to elucidate the potential anti-photoaging mechanisms of PRP. Methods : Murine dermal fibroblasts (MDFs) were isolated and cultured with or without PRP after exposure to repeated UVB irradiation per protocol. The senescent phenotypes were compared among groups, including cell morphology, senescence-associated β-galactosidase (SA-β-gal) expression, cell cycle arrest, production and degradation of extracellular matrix (ECM), ROS generation, and the alteration of major intracellular antioxidants. Results : 1% PRP effectively reduced the amount of flattened cells and significantly decreased the staining intensity as well as the percentage of SA-β-gal-positive cells when compared with UVB group. Furthermore, PRP appeared to prevent cell cycle arrest caused by irradiation by decreasing p53 and p21 expression. The PRP had demonstrated direct effects on ECM, including increase in type I collagen production and decrease in MMPs expression. Additionally, the increase of glutathione, one of the major intracellular antioxidants, induced by PRP provided a possible explanation for its therapeutic effect. Conclusions : Our work confirmed that PRP, a compound of various growth factors, could counteract senescence-like phenotypes at the cellular level, mirroring its rising clinical popularity in anti-aging and regenerative medicine. The promising effects of PRP calls for future study for further exploration of the underlying mechanisms, which will lead to a broadened application of PRP in future clinical use.